Athenacrinus n. gen. and other early echinoderm taxa inform crinoid origin and arm evolution. (March 2020) - Guensburg, Thomas E.; Sprinkle, James; Mooi, Rich; Lefebvre, Bertrand; David, Bruno; Roux, Michel; Derstler, Kraig
Abstract: Intermediate morphologies of a new fossil crinoid shed light on the pathway by which crinoids acquired their distinctive arms. Apomorphies originating deep in echinoderm history among early nonblastozoan pentaradiate echinoderms distinguish Tremadocian (earliest Ordovician) crinoid arms from later taxa. The brachial series is separated from the ambulacra, part of the axial skeleton, by lateral plate fields. Cover plates are arrayed in two tiers, and floor plates expressed podial basins and pores. Later during the Early Ordovician, floor plates contacted and nestled into brachials, then were unexpressed as stereom elements entirely and cover plates were reduced to a single tier. Incorporation of these events into a parsimony analysis supports crinoid origin deep in echinoderm history separate from blastozoans (eocrinoids, 'cystoids'). Arm morphology is exceptionally well-preserved in the late Tremadocian to early Floian Athenacrinus broweri new genus new species. Character analysis supports a hypothesis that this taxon originated early within in the disparid clade. Athenacrinus n. gen. (in Athenacrinidae new family) is the earliest-known crinoid to express what is commonly referred to as 'compound' or 'biradial' morphology. This terminology is misleading in that no evidence for implied fusion or fission of radials exists, rather it is suggested that this condition arose through disproportionate growth. UUID: http://zoobank.org/b383e039-3298-4472-a7e3-e81684f87cfe